Development of an Android and Cloud-Based Human Resource Information System: A Case Study at PT Sari Ater - Pasha, Mochammad Samy; Aspiranti, Tasya; Nurdin, Nurdin (Journal of Information System, Technology and Engineering, 2025)
Human resource operations in many Indonesian companies still rely heavily on manual systems, leading to inefficiencies, data inaccuracies, and delays. This study examines the development and implementation of an Android and cloud-based Human Resource Information System (HRIS) at PT Sari Ater, a hospitality company facing such operational challenges. The objective is to reduce processing time, improve data accuracy, and enhance employee satisfaction by digitizing core HR functions such as leave requests, reimbursement claims, attendance tracking, and training records. The study adopts a qualitative descriptive method, including interviews, observations, and document analysis, and applies the Trees Rapid Track Cloud Implementation Methodology. A four-week pilot involving 35 employees showed significant improvements: leave approval times dropped from over 4 days to under 1 day, reimbursement processing was reduced by 65%, and form entry errors declined by over 80%. Employee satisfaction with HR services also increased substantially. These findings demonstrate that integrating mobile and cloud technologies can transform HR operations in SMEs, increase transparency, and support digital transformation. The system offers a scalable model for similar organizations seeking to modernize their HR management and foster a culture of accountability and efficiency.